The Effects of TikTok on Family Relationships and Life - Panta, Saroj Raj (Dhaulagiri Journal of Contemporary Issues, 2024)
This article examines the influence of TikTok on people's behavior and lives, specifically how it has changed the way individuals interact with technology. It also explores the potential of TikTok to improve family life, mental health, and physical well-being. The study aims to understand how social media platforms like TikTok can impact behavior, social dynamics, and cultural values in Baglung and its surrounding areas. The research focuses on the effects of virtual entertainment on daily life, particularly how TikTok affects family relations and working family relationships, as well as its role in causing migrant family infidelity. A mixed qualitative and quantitative approach was utilized, involving 162 participants selected through purposive sampling. Data was collected through observation, interviews, questionnaires, and review of secondary sources. The findings indicate that virtual entertainment has a detrimental impact on family unity, social cohesion, traditional rituals, culture, customs, practices, values, beliefs, and community bonds. This poses challenges for Eastern societies despite the positive aspects of technology. Family solidarity, closeness, and agreement are diminishing as individuals become absorbed in their own devices. The use of modern technology has introduced new challenges to interconnected societies. This research is crucial for understanding the impacts of social media, TikTok, and online entertainment on individuals and families, and for guiding future studies in this field. It will be helpful to activists, academicians, future researchers, and policymakers.